Influence of Group Cognitive Behavioral Therapy on Pregnancy Outcomes among Pregnant Women with Gestational Diabetes Mellitus: a Propensity Score Matching Study - CHE Guoyu, MA Aqin, YANG Lan, LI Jing, WANG Ling (Zhongguo quanke yixue, 2023)
Background Gestational diabetes mellitus (GDM) is a common complication during pregnancy. However, the adherence to individualized medical nutrition therapy (IMNT) alone among GDM women is poor and the impact of group cognitive behavioral therapy (GCBT) on their pregnancy outcomes remains unclear. Objective To examine the impact of GCBT on the pregnancy outcomes of women with GDM, and to provide reference for improving pregnancy outcomes and developing effective gestational diabetes management programme. Methods A total of 878 pregnant women with GDM who delivered and received IMNT in our hospital from 2020 to 2021 were retrospectively selected as the study subjects and divided into the observation group including 141 pregnant women with GDM who received GCBT and the control group including 737 pregnant women with GDM who did not receive GCBT. The differences in pregnancy outcomes of pregnant women with GDM between the two groups before and after propensity score matching were analyzed. Results There were 134 pregnant women with GDM in the observation group and 256 pregnant women with GDM in the control group after 1∶2 propensity score matching. The proportion of pregnant women with GDM who gained normal weight in the observation group (50.7%, 68/134) was higher than that in the control group (37.5%, 96/256) (P<0.05) . The gestational weeks of delivery of pregnant women with GDM in the observation group (39.0±1.1) were longer than those in the control group (38.5±1.7) (P<0.05) . Additionally, the proportions of preterm infants (3.7%) , macrosomia (1.5%) , and low birth weight infants (2.2%) were lower than those in the control group (10.5%, 5.9%, and 9.0%, respectively) (P<0.05) . Conclusions GCBT can help reduce the risk of the delivery of preterm infants, low birth weight infants, and macrosomia in pregnant women with GDM, providing a reference for the establishment of a multidisciplinary management model for GDM.